Camera Trapping Wildlife on Mount Penrissen Area in Western Sarawak - Kaicheen, Sally Soo; Jayasilan, Mohd-Azlan (Malaysian Society of Applied Biology, 2018)
Camera trapping is a useful technique to study larger terrestrial mammals. Intensive camera trap surveys were carried out in Mount Penrissen (1350 asl.) area in order to understand the distribution of many elusive and cryptic species along the elevation gradient. This survey resulted in 45,145 photographs from an effort of 7,382 camera trap days from April 2015 to March 2017 (24 months). This survey recorded 33 species which include 11 birds, two small mammals and 20 larger mammals. Most of the larger mammals were recorded within the elevation range of 900 – 1100 m a.s.l. where mixed dipterocarp forest transit into lower montane forest in Mount Penrissen. Conservation importance species includes the Sunda Pangolin (Manis javanica) (critically endangered), Binturong (Arctictis binturong), Pig-tailed Macaque (Macaca nemestrina), and Bearded Pig (Sus barbatus) (vulnerable). Nearly 15% of the recorded species are considered totally protected in Sarawak under the Wild Life Protection Ordinance (SWLPO) 1998 and over 45% are listed as protected. The occurrence of these species in this area suggest that this continuous forest that extend into Kalimantan, Indonesia, may support the long-term persistence and landscape-scale movement of the threatened, sensitive and species of conservation importance in Sarawak.